Determinação de contaminantes orgânicos em matrizes complexas utilizando método QuEChERS e cromatografia líquida acoplada à espectrometria de massas de alta resolução - Munaretto, Juliana Scariot (2016)
The presence of organic contaminants in the environment and in food have become a major concern due to the harmful effects to living organisms. Such contaminants may be pesticides used in agriculture for the control of pests, transformation products formed in the environment or through chemical processes, such as water treatment, and more recently pharmaceuticals and personal care products. Therefore, it is necessary to use sample preparation procedures and detection systems able to detect a variety of organic contaminants in trace level present in complex matrices, such as food and environmental samples. Thus, this study aims to: (1) address the use of high resolution mass spectrometry (HRMS) for the identification and quantification of organic contaminants in fish fillet using two acquisition data modes (full scan and all ions MS/MS) and to optimize QuEChERS method as sample preparation (PAPER 1); (2) present a second quantitative application of the use of QuEChERS method and HRMS for fruit samples (apple, pear and grape) in full scan mode, as well as to apply the proposed method for commercial fruit samples (PAPER 2) and (3) optimize and use QuEChERS method for extracting ionophore antimicrobials in poultry litter, followed by its quantification by LC-MS/MS and identification of transformation products by LC-QToF/MS after three different composting processes (PAPER 3). The three papers presented the importance of sample preparation optimization, QuEChERS, in order to obtain proper recovery of organic contaminants, besides to minimize the matrix effects caused by interferences in the extract. As the use of HRMS, which proved to be a very effective analytical tool for combining high resolution and mass accuracy, for identification and quantification of target organic contaminants, transformation products and metabolites in complex matrices using a rapid chromatographic run.